A Review on Current Osteoporosis Research: With Special Focus on Disuse Bone Loss. (16th August 2011) - Lau, Roy Yuen-chi; Guo, Xia
Abstract : Osteoporosis is a multifactorial skeletal disorder characterized by decreased bone mass and deteriorated microarchitecture that lead to increased risk of fracture. The disuse osteoporosis refers to bone mass decrements under conditions of decreased mechanical loading, including decreased ground force reaction, muscular contraction, and microgravity-related bone loss in astronauts after space flights. Although there are many effective treatments available for primary osteoporosis, there is a lack of effective treatments for disuse osteoporosis. This is because that the aetiology, pathophysiology, and resultant pathology of disuse osteoporosis differ from those of primary osteoporosis. The objective of this paper is to examine the unique pathology and underlying pathophysiology of disuse osteoporosis.